Läkartidningen medical journal 2004 - Språkbanken Text (University of Gothenburg, 2024)
Part of the corpus for health care technical language

Del av Korpus för vårdens och omsorgens fackspråk
Läkartidningen 2004
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik